2022
DOI: 10.18388/abp.2020_6245
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufagin inhibits proliferation and induces apoptosis of hepatocarcinoma cells by activating apoptosis, AKT, and ERK pathways

Abstract: Cinobufagin is one of the pharmaceutically active ingredients in the parotoid glands of the Chinese toad Bufo bufo gargarizans Cantor. This study was conducted to investigate the effect of cinobufagin on viability, migration, and apoptosis of hepatocellular carcinoma (HCC) cells and its mechanisms. Human HCC cells (HepG2) were treated with cinobufagin and assessed for viability, apoptosis, and migration using CCK-8 assay, flow cytometry, and wound healing assay. The expression of genes related to the p53, AKT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Several studies have shown that CBF can inhibit proliferation of hepatocellular carcinoma cells. Wendong Feng et al used CCK-8 assay to examine the growth of cells treated with CBF [ 16 ]. The results showed that when CBF concentration increased from 0 to 320 ng/l, the inhibition of HepG2 cells increased from 0% to 65% at 12 h, to 87% at 24 h, and to 99% at 48 h, and the LD50 of CBF was estimated to be 170, 78, and 40 ng/L, respectively.…”
Section: Pharmacological Activities Of Cbfmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that CBF can inhibit proliferation of hepatocellular carcinoma cells. Wendong Feng et al used CCK-8 assay to examine the growth of cells treated with CBF [ 16 ]. The results showed that when CBF concentration increased from 0 to 320 ng/l, the inhibition of HepG2 cells increased from 0% to 65% at 12 h, to 87% at 24 h, and to 99% at 48 h, and the LD50 of CBF was estimated to be 170, 78, and 40 ng/L, respectively.…”
Section: Pharmacological Activities Of Cbfmentioning
confidence: 99%
“…Mechanistic studies indicated that CBF could inhibit proliferation and induce apoptosis of HepG2 cells by upregulating the p53 pathway and downregulating the Akt and ERK pathways [ 16 ]. In addition, CBF triggers defects in spindle formation and cap-dependent translation in liver cancer cells by inhibiting the AURKA-mTOR-eIF4E axis [ 17 ].…”
Section: Pharmacological Activities Of Cbfmentioning
confidence: 99%